Laringitis aguda obstructiva o crup viral - Bustos P., María Fernanda; Guzmán N., Miguel; Galeno S., Cristina (Revista Hospital Clínico Universidad de Chile, 2014)
We present the problem of viral croup or acute laryngotracheitis as an important respiratory issue in children that often prompts parents to seek physician consultation. Despite its frequency, there is still controversy among the medical team regarding its treatment. The problem will be defined and analyzed in-depth in terms of pathogenesis, to finally suggest a simple, clinically effective treatment than can be applied in any emergency service. We highlight the importance of epinephrine and corticosteroids in the acute treatment of these patients.